Ratio Decidendi in the Decision of State Administrative Case No.160/G/2018/PTUN.SBY - Ponco Eko, Moh. Saefulloh; Muhibbin, M.; Suratman, Suratman (Ridwan Institute, 2024)
This study aims to examine the ratio decidendi which is the basis for the judge in issuing a decision in case No.160/G/2018/PTUN.SBY. In the litigation process, the ratio decidendi is an important aspect to determine whether the arguments of the lawsuit are rejected, granted, or partially granted. This research is included in the type of juridical-normative research conducted with a statutory approach (statue approach) and a case study approach (case study). This research uses secondary legal sources from various laws and regulations relating to state administrative courts, as well as legal materials from books, journals, and other literature studies relevant to legal issues. The results showed that the Panel of Judges of PTUN Surabaya considered the settlement of the case by using 3 testing parameters, namely in terms of authority to issue, in terms of formal procedures for issuance and in terms of the material substance of the object of dispute. the results showed that the ratio decidendi of the judge in Decision No.160/G/2018/PTUN.SBY, including, among others, the authority of the defendant as a state official, the formal procedure of the mechanism for issuing the letter that became the object of dispute, and the formal substance of the lawsuit.